Mazhab Pendidikan Kritis; Proses Humanisasi Pendidikan - Musa Al-Fadhil (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
Education is considered as one way to liberation from underdevelopment ability financially or as a means to maintain the financial strength of the family. It is undeniable that the financial matter is very important, especially to measure human well-being, but knowledge is too oriented towards the focal point that has already set the dehumanization of man. Freire criticized the too-oriented education at the focal point of financial and material alone. He calls in education nuanced